In silico development and evaluation of pyruvic acid derivatives as potential analgesic and anti-inflammatory agents - Kurniawan, A. Hafidz (Journal of Earth Kingdom, 2025)
Background: Drug development is a process aimed at creating new drugs with enhanced biological activity through various approaches. One such approach is the rational design of new compound candidates using computer-based or in silico modeling technologies, such as molecular docking. Pyruvic acid is known to possess various pharmacological activities, including antioxidant and anti-inflammatory effects. Derivatives of pyruvic acid have the potential to be developed as candidate analgesic and anti-inflammatory drugs. This study explores the in silico development and evaluation of pyruvic acid derivatives as potential analgesic and anti-inflammatory drug candidates. Methods: Drug-likeness was evaluated using Lipinski's Rule of Five via pkCSM, while pharmacokinetic and toxicity profiles were predicted using the same platform. Molecular docking was performed on the cyclooxygenase-2 (COX-2) enzyme (PDB ID: 5IKR) using Molegro Virtual Docker 6.0. Findings: All test compounds met drug-likeness criteria. Compounds H6, H8, H9, H11, H17, and H18 exhibited superior binding affinities compared to paracetamol. Several compounds, including H8 and H10, demonstrated lower predicted toxicity compared to paracetamol. All test compound exhibits favorable pharmacokinetics properties based on the pkCSM preditive model. Conclusion: From this results, compound H6 and H8 emerged as the most promising candidate, exhibiting optimal characteristics across all evaluated parameters. These findings support further development of H6 and H8 as potential analgesic and anti-inflammatory agent targeting COX-2 Inhibition. Novelty/Originality of this article: This study developed and evaluated pyruvic acid derivative compounds as novel analgesic and anti-inflammatory agents based on in silico studies.